HTML5 games: Creating fun with HTML5, CSS3, and WebGL - Seidelin, Jacob (Chichester, England : Wiley, 2014)
HTML5 Gamesshows you how to combine HTML5, CSS3 and JavaScript to make games for the web and mobiles - games that were previously only possible with plugin technologies like Flash. Using the latest open web technologies, you are guided through the process of creating a game from scratch using Canvas, HTML5 Audio, WebGL and WebSockets. Inside, Jacob Seidelin shows you how features available in HTML5 can be used to create games. First, you will build a framework on which you will create your HTML5 game. Then each chapter covers a new aspect of the game including user input, sound, multiplayer functionality, 2D and 3D graphics and more. By the end of the book, you will have created a fully functional game that can be played in any compatible browser, or on any mobile device that supports HTML5.
Part I. Getting started with HTML5 games -- part II. Creating the basic game -- part III. Adding 3D and sound -- part IV. Local storage and multiplayer games.
Includes index.
Keywords: COMPUTER GAMES -- PROGRAMMING